(untitled) (Spandan, 2023)
This study investigates the integration of Information and Communication Tools and Technology (ICT) in secondary government schools within the Bhaktapur district, highlighting both usage and challenges. A quantitative research design surveyed 462 ICT teachers and students across 22 schools. The findings show that teachers and students effectively use a variety of ICT tools to enhance teaching and learning. These include hardware and software tools, communication and collaboration platforms, and E-learning systems. Despite these advancements, challenges such as slow internet bandwidth, insufficient hardware, lack of trained personnel, and poor school management hinder the optimal use of ICT tools. 70 percent of teachers update their ICT skills independently, with minimal governmental training support. The School Sector Development Plan has significantly contributed to developing ICT infrastructure in 39 percent of schools, but issues like inadequate Wi-Fi signals, insufficient practical classes, and large student numbers persist. Moreover, 65 percent of teachers rely on school administration to resolve ICT-related issues, and 95 percent of students have access to ICT tools, though usage is sometimes disrupted by power outages and internet issues. The study underscores the necessity for continuous improvement in internet connectivity, regular teacher training, and better management of ICT resources. The Government of Nepal’s efforts through the School Sector Development Plan are promising, but sustained efforts are needed to overcome the existing barriers. By addressing these challenges, schools can fully harness the potential of ICT tools to create a more engaging and effective educational environment.